The Role of Landscape in the Formation of Ecotourism Objects on the Territory of Uzbekistan - M., G`aybullaeva (International Journal on Integrated Education, 2023)
In the article, the authors provide information (landscape solutions for historical monuments, etc.). An attempt is made to analyze the tourist and landscape solution of historical monuments of Samarkand.